Automatic Prototype Design Based on Pir Sensor and Microcontroller Arduino Uno - Wibawa, Muhammad Bayu; Rahmad, Muhammad (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2017)
The use of electronic devices cannot be separated from the electricity usage. Meanwhile, the continuously device use willimpact on the electricity cost incurred to the users. An electricity price is increasing steadily, particularly in Aceh province, while the power base is still insufficient. A Light bulb for the lighting purposes in one of the electricity devices used in households, offices and other institutions. Switching on the bulb for unoccupied room is not rare to happen, which lead to the inefficiency usage of electricity. An automatic control device which incorporates the sensor technology is needed to address the issue. This automatic sensor deviceuses a passive infra red sensor and microcontroller Arduino Uno. Implementing this sensor system, the incurred electricity cost to the customers can be reduced. This technology can be used in households, offices and other institutions.Keywords : Prototype Automatic light , Microcontroller Arduino Uno , Infra Red Sensor